Clinical Sports Medicine & Orthopedics - Lion A; 2; 3; Lethal J; Delagardelle C; 2; 3; 4; Seil R; 5; 6; Urhausen A; et al. (Dynamic Media Sales Verlag, 2022)
A physical activity (PA) promotional campaign was launched in June 2018 to raise awareness of the health benefits of PA in patients with chronic diseases in Luxembourg. This study aimed to evaluate the behavior of general practitioners (GPs) regarding PA counselling before and after the campaign. The campaign consisted of advertisement broadcasts on national TV/radio in June and July 2018 and comprised a toolkit (flyers and a PA evaluation tool) sent in September 2018 to all medical doctors registered in Luxembourg. PA counselling behaviors were evaluated in 59 and 53 GPs who answered a standardized questionnaire before and after the campaign, respectively. Interviewed GPs declared having advised only a small proportion of their patients regarding PA participation before and after the campaign (29% and 24%, respectively; p<0.001). The campaign had no impact on the GPs awareness (21%) about the national program offering PA for patients with chronic diseases. Lack of time and knowledge were identified as the main barriers to engaging in PA counselling. Overall, GPs encouraged only a small proportion of their patients to engage more in PA, and the awareness campaign failed to change their PA counselling behavior, at least in the short term. Barriers to PA promotion within primary healthcare should be addressed before implementing new awareness campaigns targeting healthcare professionals.Key Words: Medical Doctors, Primary Healthcare, Exercise Counselling, Health Promotion